Teen angst? Naaah... a quasi-autobiography - Vizzini, Ned 1981-2013 (Free Spirit Publishing, 2000)
A collection of essays written by the author from age fifteen to seventeen in which he shares impressions of school, sports, cool people, boring people, friends, family, money, music, and obsessions
Includes index
Keywords: Vizzini, Ned, -- 1981-2013; Vizzini, Ned; Teenagers -- New York (State) -- New York -- Biography -- Juvenile literature; High school students -- New York (State) -- New York -- Biography -- Juvenile literature; Teenagers; Youths' writings; Biografie